2021
DOI: 10.3390/agronomy11050908
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL for Tolerance to Flooding Stress at Seedling Stage of Soybean (Glycine max L. Merr.)

Abstract: Flooding stress is a serious problem in soybean production, causing a remarkable yield reduction. The onset of rainy season during the early growth of soybean in Korea and some other parts of the world potentially subjects soybean plants to flooding stress. The objective of this study was to map quantitative trait loci (QTL) for flooding tolerance using a recombinant inbred line (RIL) population derived from a cross between ‘Danbaekkong’ (flood-tolerant) and ‘NTS1116′ (flood-susceptible) cultivars grown in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…In another study, several QTL were mapped for soybean flood tolerance at the seedling phase. Two significant QTL were detected on chromosomes 7 and 3 under DWI in 2017 and 2018, exhibiting the highest (25.6%) and lowest (8.3%) phenotypic variance, correspondingly ( Dhungana et al., 2021b ). Seed water logging tolerance is critical to sustaining soybean growth and production under flood stress.…”
Section: Qtl Identified For Flood Tolerance In Soybeanmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, several QTL were mapped for soybean flood tolerance at the seedling phase. Two significant QTL were detected on chromosomes 7 and 3 under DWI in 2017 and 2018, exhibiting the highest (25.6%) and lowest (8.3%) phenotypic variance, correspondingly ( Dhungana et al., 2021b ). Seed water logging tolerance is critical to sustaining soybean growth and production under flood stress.…”
Section: Qtl Identified For Flood Tolerance In Soybeanmentioning
confidence: 99%
“…QTL mapping has been widely used to unlock the novel QTL contributing to flooding tolerance in soybean. Various QTL were identified using different mapping populations to accelerate marker-assisted selection programs ( Dhungana et al., 2021b ; Zhang et al., 2022 ). Genome-wise association studies (GWAS) have identified new genes for soybean response to flood stress ( Sharmin et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This QTL accounts for 30.25% variation in phenotype and will assist in developing of markers for root-length selection, which is an important trait for drought tolerance. Dhungana et al (2021) identified QTLs associated with flooding stress at the V1-V2 stage of soybean. They analysed a recombinant inbred line (RIL) population derived from crossing a drought-susceptible (NTS116) and drought-tolerant (Danbaekkong) soybean cultivar.…”
Section: Marker-assisted Breedingmentioning
confidence: 99%
“…Genetic mapping is essential for QTL mapping, map-based cloning, and MAS [ 29 ] and has been widely used in many major crops [ 17 , 27 , 28 , 30 ]. In the past decade, although a great quantity of TKS molecular markers (SSRs and SNPs) have been developed, they have mostly been used in research on the genetic diversity and population structure of TKS [ 7 , 20 , 21 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous SNP markers obtained by high-throughput sequencing could be used for constructing high-density genetic maps and QTL mapping for important traits [18,25], and this approach has proven effective in many major crops [17,[26][27][28]. Recently, through further splicing and optimizing the TKS genome constructed in 2018 [2], a TKS genome sketch at the chromosome level was published in 2021, which provided a solid foundation for high-density SNP genetic map construction, QTL fine mapping and MAS for TKS breeding [1].…”
Section: Introductionmentioning
confidence: 99%